A Promising Approach of Dermal Targeting of Antipsoriatic Drugs via Engineered Nanocarriers Drug Delivery Systems for Tackling Psoriasis - Tripathi, Devika; Srivastava, Mansi; Rathour, Krislay; Rai, Awani K.; Wal, Pranay; Sahoo, Jagannath; Tiwari, Ritesh Kumar; Pandey, Prashant (Drug Metabolism and Bioanalysis Letters, 2023)
Psoriasis is a complex autoimmune skin condition with a significant genetic component. It causes skin inflammation and is characterized by flaky, silvery reddish spots that can worsen with age. This condition results from an impaired immunological response of T-cells and affects 2-5% of the global population. The severity of the illness determines the choice of treatment. Topical treatments are commonly used to treat psoriasis, but they can have several adverse effects. Biological therapy is another option for treating specific types of psoriasis. Recently, new nanoformulations have revolutionized psoriasis treatment. Various nanocarriers, such as liposomes, nanostructured lipid nanoparticles, niosomes, and nanoemulsions, have been developed and improved for drug delivery. The use of nanocarriers enhances patient compliance, precise drug delivery, and drug safety. This review aims to suggest new nanocarrier-based drug delivery systems for treating psoriasis. It discusses the importance of nanocarriers and compares them to traditional treatments. Anti-psoriatic drugs have also been investigated for cutaneous delivery using nanocarriers. The review also covers various factors that influence dermal targeting. By highlighting several relevant aspects of psoriasis treatment, the review emphasizes the current potential of nanotechnology. Using nanocarriers as a drug delivery technique may be a promising alternative treatment for psoriasis.
Keywords: dermal targeting